Investigation of Academic Enthusiasm among the Students of Golestan University of Medical Sciences in 2023 - Saba Poolaie; Amirhossein Babanezhad; Akram Sanagoo; Fatemeh Mehravar; Jouybari (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Academic enthusiasm is a form of psychological investment and a direct effort to learn, understand, and master the necessary knowledge and skills. Moreover, it is considered one of the positive factors contributing to students' academic success. The present study aims to assess the level of academic enthusiasm among medical students and its relationship with various demographic and educational variables. Methods: This cross-sectional study was conducted among students at Golestan University of Medical Sciences in 2023. A total of 444 students were enrolled using convenience sampling. Data were collected using a demographic and educational characteristics form and the Student Engagement Scale (SES) questionnaire. The data were analyzed using SPSS software (version 18), employing descriptive and inferential statistics (independent t-test and one-way ANOVA) at a significance level of 0.05. Results: The mean score for academic enthusiasm was 66.21±19.32 (out of a possible 130 points). A significant relationship was observed between academic enthusiasm scores and the variables of field of study (P=0.001), educational level (P=0.001), and marital status (P=0.003). The findings indicated that overall academic enthusiasm was highest among clinical-year medical students(76.89 ± 20.51), and lowest among master’s students in nursing and genetics (59.26 ± 13.33). Additionally, academic enthusiasm significantly higher in single students (105.00 ± 22.34) compared to married students (87.30 ± 19.20). The highest mean academic enthusiasm was observed among medical students (72.14 ± 19.24), whereas health science students exhibited the lowest mean (58.33 ± 13.62). Conclusion: The average level of academic engagement among students at Golestan University of Medical Sciences was moderate, clinical-year medical students exhibited higher levels of academic enthusiasm compared to students in other academic levels. This finding can be viewed as both an opportunity and a challenge for educators, particularly for instructors in clinical and practical courses. The lower levels of academic enthusiasm were observed among master’s students in nursing and genetics warrant further evaluation, and it seems essential to review the curriculum content to enhance and enrich the educational experience for these students.